The diameter effect on the magnetization switching time of sphere-shaped ferromagnets using micromagnetic approach. Issue 1 (July 2020) - Kurniawan, C; Widodo, A T; Djuhana, D
Abstract: In this work, the magnetization switching time has been studied as the diameter variation of sphere-shaped ferromagnets by means of micromagnetic simulation. Some ferromagnetic elements such as cobalt, iron, nickel, and permalloy were numerically simulated with diameter size variation from 50 nm to 100 nm. The micromagnetic simulation was performed by public software Object Oriented Micromagnetic Framework (OOMMF) based on the Landau-Lifshitz-Gilbert (LLG) equation. The ferromagnetic nano-sphere was induced by the quasi-static magnetic field to observe its magnetization response. Generally, it is observed that the switching time increases as the diameter size increases on the ferromagnetic elements. However, the switching time are relatively insensitive as the diameter increases in the Cobalt element for the diameter range from 60 nm to 90 nm. This behavior is contributed to the distribution of magnetization easy axis on the ferromagnetic elements. The understanding of domain structures during magnetization switching process is important in the development of nano-patterned magnetic memory storage.